Pharmacological Studies of Different Fractions of Litsea monopetala Roxb. - Bulbul, Israt Jahan; Rashid, Mohammad A; Haque, Mohammad Rashedul (Bangladesh Pharmaceutical Journal, 2020)
Abstract not available Bangladesh Pharmaceutical Journal 23(1): 61-64, 2020